Comparative next-generation sequencing of adeno-associated virus inverted terminal repeats. (May 2014) - Petri, Karl; Fronza, Raffaele; Gabriel, Richard; Käppel, Christine; Nowrouzi, Ali; Linden, R. Michael; Henckaerts, Els; Schmidt, Manfred
The inverted terminal repeats (ITRs) of adeno-associated virus (AAV) are notoriously difficult to sequence owing to their high GC-content (70%) and palindromic sequences that result in the formation of a very stable, 125 bp long, T-shaped hairpin structure. Here we evaluate the performance of two widely used next-generation sequencing platforms, 454 GS FLX (Roche) and MiSeq Benchtop Sequencer (Illumina), in analyzing ITRs in comparatively sequencing linear amplification-meditated PCR (LAM-PCR) amplicons derived from AAV-concatemeric structures. While our data indicate that both platforms can sequence complete ITRs, efficiencies (MiSeq: 0.11% of sequence reads; 454: 0.02% of reads), frequencies (MiSeq: 171 full ITRs, 454: 3 full ITRs), and rates of deviation from the derived ITR consensus sequence (MiSeq: 0.8%–1.3%; 454: 0.5%) did differ. These results suggest that next-generation sequencing platforms can be used to specifically detect ITR mutations and sequence complete ITRs.